Internalisasi Konsep Zuhud dalam Membentuk Karakter Religius Siswa Pendidikan Dasar Islam - Muhammad Hifni Najih Yasak; Ali Mas’ud; Muhibbin Zuhri (AL-ASASIYYA: Journal Of Basic Education, 2022)
This study aims to understand and describe the internalization of the concept of zuhud in the formation of the religious character of students at the Fadllillah Islamic Boarding School, Waru, Sidoarjo. This research uses a qualitative approach, with the type of case study. In this study, the researcher acts as a key instrument with the object of research being Kiai, teachers, and students. The research data were collected through interviews, observation, and documentation, while the data analysis techniques consisted of data reduction, data display, and conclusions. This study resulted in the findings that: (1) the strategy of internalizing the concept of zuhud in the formation of the religious character of students was applied through mujahadah and uswah hasanah activities; (2) the stages of internalization consist of: providing direction, both inside and outside the classroom; provide direct examples; familiarize students to be disciplined in accordance with the rules that have been set; and impose penalties for each student who violates the rules; and (3) supporting factors, namely: high willingness of students; support from family; and encouragement from peers to apply the concept of zuhud in daily life; and (b) inhibiting factors, namely: lack of obedience and obedience of students; peer influence; and lack of encouragement from their own family.